AO REDOR DA MESA: A CIRCULAÇÃO DA PALAVRA IMPRESSA NA SEGUNDA METADE DO SÉCULO XVIII LUSITANO - Silva, Hevilton Wisnieski da (2017)
Being in contact with sources and having a bibliography with excellent analysis is what the historian expects. And when the sources are produced by the bibliography itself? The history of the book and the reading exposes this pleasant paradox, and the circulation of books under the control of Portuguese censorship in the second half of the eighteenth century provided a broad documentary collection that allows to analyze the Luso-Brazilian cultures in this context and the attempts to build barriers That would limit these cultures to the understanding of what could or could not be remembered or forgotten. From this documentation, a quantitative analysis will be carried out on the type of books circulating in the Atlantic, disembarking in Rio de Janeiro, time in Oporto and qualitative, giving meaning to the vestiges present in applications that were written to the censorship requesting permissions to be able to do To circulate these books both in their aesthetic product of the official regiemento and the customs acquired by the ordinary action of investigating and controlling, as well as between the lines that indicated behaviors and interests produced by the books in their circulation. The demands of censorship have acquired a paradox that has built up not obedient and honest people as to the rules for transporting or sending books, but people who were part of the legal world at the same time as they smuggled the illegal world of book smuggling. At this juncture the documentation, although most of them require legal book lists, some problems still occur, with some being held at the customs for investigation or even sent to the Bureau because they are forbidden to travel. On paper, the manuscripts translate control based on the Portuguese illustration, of a utilitarian character, which valued scientific development, but at the same time it moved away from the most radical ideas existing in the eighteenth century in Europe, in defense of the Catholic faith and of the royal power . Robert Darnton points out that the tool of censorship, far from being merely the exercise of cutting, suppressing, prohibiting and punishing, served as an endorsement of the world of books, adding positive values that elevated publishing and profit in the book market. In Portugal, as in France, which Darnton studied in the same context, censors participated in the book market, according to Curto, the president of the Real Mesa Censoria of the Pombal period, Manuel do Cenáculo, was also one of the most active consumers of books, Of the most important Lusitanian scholars, as observed by Rui Tavares. It is not by chance that the Cenacle maintained close relations with booksellers like Jorge Rey, who was also a book editor. That is why around the table the books circulated and built roads that led the book market to one of the wealthiest businesses of the eighteenth century, mainly through clandestinity, but also in legality, in view of some lists of books by resident French booksellers In Portugal that are part of the documentation, which contained about two, three hundred books of the most varied titles and were destined for Rio de Janeiro. Of breaking this movement has a sense produced.